.Analisa Proses Tahapan Akuisisi Bank ABC oleh PT XYZ dan PT DEF - Effendi, Ridwan; Abidin, Zaenal (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The development of Mergers and Acquisitions is a form of corporate growth strategy to access new products and markets and is considered a fast way. PT Bank ABC was acquired by PT DEF which aims to compete in the Digital Bank business which is currently developing in Indonesia. In general, a bank that is acquired will have a positive effect on its financial performance, but this needs to be reviewed in non-financial matters such as work culture or constraints in making strategic decisions on the continuity of PT Bank ABC's business, the research method used is a qualitative research method with a descriptive method by comparing the performance and work culture of PT Bank ABC before the acquisition and after the acquisition. The data used in this research consists of primary data and secondary data obtained from various sources, primary data obtained directly from interviews with several Middle Top Management of PT Bank ABC while secondary data obtained from monthly publication reports of PT Bank ABC before the acquisition process and after the acquisition process. Broadly speaking, the acquisition process of PT Bank ABC has been carried out in accordance with the POJK provisions and while in terms of performance or work culture there are differences after the takeover of shares. Keywords: merger & acquisition, process evaluation, performance & work culture.